PENGARUH MEDIA AUDIO VISUAL BERBASIS ANIMASI TERHADAP MOTIVASI BELAJAR SISIWA PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 6 PALEMBANG - Wahyu Romadhona; Yulia Djahir; Ikbal Barlian (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2014)
The formulation of problem in this research is "Is there any influence of animated audio-visual media toward student's learning motivation on economic subjects of class X odd semester at SMA Negeri 6 Palembang year lesson 2012/2013", The research is experimental type True Experimental design with Posttest-Only Control Design with three treatments. In this study the population is all the students of class X SMA 6 Palembang that terdidri of 7 classes of academic year 2012/2013 with the number of students 224 students. The sample in this study was taken using simple random sampling technique and got two classes that is X_3 As the experiment class which amounted to 32 students and class X_2 as control class which amounted to 32 students. Data collection techniques were obtained using angkeet technique and observation. The statistic used to analyze data is using t-test with significant level (α ═ 0,05). Based on animation analysis to student's learning motivation, where result of t-test show that t_ value (count) = 11,2> t_ (table) = 1,996 so that this research Ha accepted and Ho rejected that there is influence of audio-visual audio-based media to motivation student learning.